Question
upstudy study bank question image url

4.6. \( 3 \times 3^{x}+9 \times 3^{-x}-28=0 \)

Ask by Bartlett Phillips. in Portugal
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

As soluções da equação são \( x = 2 \) e \( x = -1 \).

Solution

Para resolver a equação   3 × 3ˣ + 9 × 3⁻ˣ − 28 = 0, vamos fazer a seguinte substituição: seja u = 3ˣ, de modo que 3⁻ˣ = 1/3ˣ = 1/u. Assim, a equação fica:   3u + 9(1/u) − 28 = 0. Multiplicando ambos os lados por u (considerando u ≠ 0):   3u² + 9 − 28u = 0  ⟹  3u² − 28u + 9 = 0. Esta é uma equação do segundo grau em u. Aplicando a fórmula de Bhaskara:   u = [28 ± √(28² − 4×3×9)] / (2×3). Calculando o discriminante:   Δ = 28² − 4×3×9 = 784 − 108 = 676. Como √676 = 26, temos:   u = (28 ± 26) / 6. Obtemos duas soluções para u: 1) u = (28 + 26) / 6 = 54/6 = 9, 2) u = (28 − 26) / 6 = 2/6 = 1/3. Lembrando que u = 3ˣ, separamos os casos: 1) 3ˣ = 9. Como 9 = 3², temos x = 2. 2) 3ˣ = 1/3. Como 1/3 = 3⁻¹, temos x = −1. Portanto, as soluções da equação são: x = 2 e x = −1.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To solve the equation \( 3 \times 3^{x}+9 \times 3^{-x}-28=0 \), we can first rewrite it in terms of \( 3^x \). Notice that \( 9 = 3^2 \), and thus \( 9 \times 3^{-x} = 3^2 \times 3^{-x} = 3^{2-x} \). We can let \( y = 3^x \), which transforms the equation to \( 3y + \frac{9}{y} - 28 = 0 \) by rewriting \( 3^{-x} \) as \( \frac{1}{y} \). Multiplying through by \( y \) to eliminate the fraction gives \( 3y^2 - 28y + 9 = 0 \). This is a quadratic equation that can be solved using the quadratic formula \( y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \). Calculating the discriminant: \( D = (-28)^2 - 4 \cdot 3 \cdot 9 = 784 - 108 = 676 \). Now, applying the formula: \[ y = \frac{28 \pm \sqrt{676}}{6} = \frac{28 \pm 26}{6}. \] This gives two possible solutions for \( y \): 1. \( y = \frac{54}{6} = 9 \) 2. \( y = \frac{2}{6} = \frac{1}{3} \) Recalling that \( y = 3^x \), we have: 1. \( 3^x = 9 \) implies \( x = 2 \) 2. \( 3^x = \frac{1}{3} \) implies \( x = -1 \) Thus, the solutions to the equation are \( x = 2 \) and \( x = -1 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy